Positivity Bias and Influencing Elite Attitudes on Women’s Leadership Evidence from Nigeria - Ragasa, Catherine; Kyle, Jordan; Ma, Ning (International Food Policy Research Institute, 2023)
This is a poster presented on the gender conference “From research to impact: Towards just and resilient agri-food systems” in India. It won the "Best Poster Award".